INFLUENCE OF MARKETING COMMUNICATION CHANNELS ON URBAN DOMESTIC TOURISM IN KENYA - Kamau, Florence; K. Waweru, F.; Lewa, Peter; J. Misiko, A. (British Journal of Marketing Studies, 2015)
This study examined the influence of marketing communication channels on demand for urban domestic tourism in Kenya. The study was conducted in tourist destinations within Nairobi and Nakuru town. The sample size comprised of 384 respondents: 254 respondents from Nairobi city and 130 respondents from Nakuru town surveyed using multistage sampling procedure. Nairobi city and Nakuru town in Kenya were selected using cluster sampling. Stratified sampling was then used to divide the tourist destinations within Nairobi city and Nakuru town. Systematic sampling procedure was used to select every 3rd respondent visiting these tourist destinations. Primary data was collected through questionnaires. The survey revealed that telephone, direct mail, yellow pages, newsletters, internet, television and travel diaries television show aired on Kenya Television Network (KTN), magazines, brochures, newspaper, radio, exhibitions, tour firms and travel agencies, Sales promotion were found significant in creating awareness of tourist destinations in Kenya.